2017
DOI: 10.3329/bjsir.v52i3.34154
|View full text |Cite
|
Sign up to set email alerts
|

Culture technique of endangered Notopterus chitala (Hamilton, 1822) with Oreochromis niloticus for domestication in pond habitat

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 6 publications
2
7
1
Order By: Relevance
“…Samad et al (2005) also recorded alkaline P H (8.1 to 8.8) in the experiment of C. batrachus in ponds. The present findings were also revealing the findings of Saha et al (2003) and Samad et al (2017).…”
Section: P Hsupporting
confidence: 92%
“…Samad et al (2005) also recorded alkaline P H (8.1 to 8.8) in the experiment of C. batrachus in ponds. The present findings were also revealing the findings of Saha et al (2003) and Samad et al (2017).…”
Section: P Hsupporting
confidence: 92%
“…Assessment made on 180 day of cultivation period showed rapid reduction of O. mossambicus fry and fingerling population and continued throughout cultivation period, indicates predatory impact of C. chitala. Similar kinds of phenomenon also reported where C. chitala significantly reduced O. niloticus population [33]. Instead of that, possibilities of cannibalism by O. mossambicus adult male population for quantitative reduction of larval population cannot be ruled out [38].…”
Section: Impact Of O Mossambicus Recruitment and It's Biocontrolsupporting
confidence: 67%
“…In the 2 nd year of the study, the farmers were asked to introduce Chitala (C. chitala) at the rate 800 number of fingerlings (average 22 gm body weight) /ha, along with IMC fingerlings in Gosai Bundh again in 2019 and this time it was considered as Treatment 2 (T2). Stocking density of C. chitala has been maintained below the suggested quantity as mentioned by [33] for an O. niloticus based polyculture system. In T2, similar quality, quantity and species combinations of IMC were maintained, as done in T1.…”
Section: Experimental Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The knowledge of fish reproduction is the most important in sustainable fisheries management, as well as to sustain fish processing business especially in Barito Kuala District. Numerous studies closely related to the featherback have been devoted to describe on reproductive biology [13,32,33], fecundity [6,34,35], genetic [36,37], length-weight relationship and condition factor [15,38], feeding habits [39,40], the age and growth [41], population dynamics [19], culture strategy [42,43] and conservation measures for this species [20,44]. In addition, Wibowo and Marson [37] reported that morphometric and meristic of N. chitala from Barito River, South Kalimantan were similar to those of C. lopis and N. notopterus from Kampar River, Riau Province, but genetically different from each other.…”
Section: Fish Farmingmentioning
confidence: 99%